Respuesta :
-4x+19=2x+1 -4(3)+19=7
-2x -2x. 2(3)+1=7
-6x+19=1
-19 -19
-6x=-18
-6x/-6 -18x/-6
X=3 Y=7
-2x -2x. 2(3)+1=7
-6x+19=1
-19 -19
-6x=-18
-6x/-6 -18x/-6
X=3 Y=7
Using substitution method, the solution to the system of the equation is (3,7).
What is substitution method?
The substitution method is "the algebraic method of solving simultaneous linear equation".
According to the question,
y = -4x +19 →(1)
y = 2x + 1 →(2)
- 4x +19 = 2x+1 [since L.H.S of both equation are equal, then equate R.H.S of given equation]
- 4x - 2x = 1 - 19
-6x = -18
x = 3
Substituting x=3 in equation (2), we have
y = 2(3) +1 [substitution method]
y = 6 +1
y = 7
Hence, using substitution method the coordinate points of the graph (3,7) is the solution to the system of equations.
Learn more about substitution method here
https://brainly.com/question/11962235
#SPJ2